Validation of The Hopelessness Scale for Children in Indonesia Students - Alinda Destiana; Fitri Ariyanti Abidin (Journal of Educational, Health and Community Psychology, 2022)
The purpose of this study was to obtain a standardized Indonesian version of the adaptability scale of guidance and counseling teachers. Adaptability consists of 8 dimensions, namely; crisis, culture, work stress, interpersonal, physical, creatively, learning, and uncertainty. The adaptation process is carried out using the International Test Commission (2016) reference. This adaptation involves 276 BK teacher. The research instrument is a statement item consisting of 55 items. The data analysis technique uses content analysis and constructs analysis. The content analysis used the CVI, while the construct analysis used CFA with the AMOS 21 program. The reliability test was based internal consistency through the Cronbach Alpha coefficient. The results of data analysis show that the CVR value meets the minimum parameters. There are 30 items that are proven to have a good fit model. The reliability coefficient of Cronbach's alpha individual variable adaptability measurement is .929.